(untitled) (Texas Journal of Medical Science, 2023)
The article presents a bacteriological analysis of patients admitted to the Bukhara Regional Infectious Diseases Hospital from March 16, 2020 to February 02, 2022 with a diagnosis of coronavirus infection COVID-19 and confirmed infection with SARS-CoV-2 (positive RT-positive in real time) . PCR typical of SARS-CoV-2) Results are shown for stool samples taken from patients Pr. Vulgaris, pr. Mirobllis, Kl.phevmoniae, Enterobacter hafniae from sputum samples of St. Pneumoniae, Can. greenish; S.epidermis, S.aureus were isolated from a blood sample. Most of the isolated microorganisms were sensitive to levofloxacin, amikacin, ciprofloxacin and cefoperazone sulbactam